“Good While It Lasts”: International Alliances Between Brazilian Family Firms And Foreign Firms - Werneck, Alvaro Luiz dos Santos; da Rocha, Angela (Internext, 2019)
The study aimed at investigating how Brazilian family firms internationalize by means of strategic alliances with foreign corporations. A literature review on strategic alliances and the internationalization of family firms served as the basis for the study, which uses the case method of investigation. Two cases involving marketing alliances between Brazilian family firms and foreign firms were analyzed. The study presents an empirically-derived framework of the processes of establishing, developing, and (eventually) terminating these strategic alliances, indicating potential hazards (asymmetries of size, information, and resources) that can impact the results, particularly within a context of different cultural background of the partners.